STRATEGI PENGEMBANGAN MEDIA DAKWAH BERBASIS PENDIDIKAN KESEHATAN - Evalinda Evalinda; Siti Nuri Nurhaidah; Nurfitria Farhana; Hayatuddin Hayatuddin; Khairul Hidayat; Agus Idwar Jumhadi; Nabiel Al Musawa (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi Islam Institut Agama Islam (IAI) Al-Azhaar Lubuklinggau, 2025)
This research focuses on developing health-based da'wah as a holistic approach to increasing public health awareness within the framework of Islamic values. Health-based da'wah integrates religious teachings with modern health principles to encourage sustainable behavior change. In Islam, maintaining health is seen as a spiritual responsibility, as explained in the Koran and hadith, such as the importance of cleanliness, healthy eating patterns, and maintaining physical, mental and spiritual balance. The research method uses a qualitative-descriptive approach by examining Islamic literature and public health practices. This research found that da'wah bil hal, namely da'wah through concrete actions, is an effective method for conveying Islamic values ​​that are relevant to health. Examples include educating the public about the importance of maintaining cleanliness through the teaching